2022
DOI: 10.1186/s12905-022-01837-4
|View full text |Cite
|
Sign up to set email alerts
|

Association between dietary total antioxidant capacity and hypertension in Iranian Kurdish women

Abstract: Background Antioxidants intake from diet has been identified as one of the effective factors in the development of hypertension (HTN). The present study aimed to investigate the association between total antioxidant capacity (TAC) and HTN in women. Methods This cross-sectional study was performed using the baseline phase data of the ravansar non-communicable disease cohort study. The TAC was calculated using food items of the food frequency questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 29 publications
0
10
1
Order By: Relevance
“…Fruits are an excellent source of phytochemicals, fiber, and antioxidants that may help with weight control ( 32 ), inhibit the development of reactive oxygen species and systemic oxidative damage ( 33 , 34 ). Berries are an excellent source of flavonoids, tannins, phenolic acids, and lignans, among other polyphenols ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Fruits are an excellent source of phytochemicals, fiber, and antioxidants that may help with weight control ( 32 ), inhibit the development of reactive oxygen species and systemic oxidative damage ( 33 , 34 ). Berries are an excellent source of flavonoids, tannins, phenolic acids, and lignans, among other polyphenols ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nutrition is generally understood to play a role in the development of noncommunicable illnesses. Previous studies have also shown that changing one's diet to include more fruits and vegetables and less sweets is one of the greatest approaches to avoiding hypertension and enhancing lipid profiles (Fateh et al, 2022(Fateh et al, , 2023. Lower intakes are linked to disorders including diabetes mellitus and metabolic syndrome (MetS) (Choi et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Among these indices, the Mediterranean diet score and the healthy eating index have gained prominence. A key element in both scores involves the incorporation of higher quantities of vegetables and fruits into the diet, and research has established a clear connection between these indices and a reduced risk of diverse ailments, including hypertension and kidney stones (Fateh et al , 2022; Moludi et al , 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Total antioxidant capacity (TAC) is a term that re ects the antioxidant potential of dietary sources [17,18], which are mainly a combination of various vitamins [19][20][21]. Researchers believe that TAC participates in the progression of several diseases, such as hypertension and cancer [22,23]. However, the relationship between TAC and muscle loss has been scarcely studied.…”
Section: Introductionmentioning
confidence: 99%